First do no harm: the impact of financial incentives on dental X-rays - Chalkley, Martin; Listl, Stefan (Journal of health economics, 2018)
This article assesses the impact of dentist remuneration on the incidence of potentially harmful dental X-rays. We use unique panel data which provide details of 1.3 million treatment claims by Scottish NHS dentists made between 1998 and 2007. Controlling for unobserved heterogeneity of both patients and dentists we estimate a series of fixed-effects models that are informed by a theoretical model of X-ray delivery and identify the effects on dental X-raying of dentists moving from a fixed salary to fee-for-service and patients moving from co-payment to exemption. We establish that there are significant increases in X-rays when dentists receive fee-for-service rather than salary payments and when patients are made exempt from payment.